Patterns of calcium signaling: A link between chronic emotions and cancer - Pregnolato, Massimo; Damiani, Giuseppe; Pereira, Alfredo [UNESP] (Ios Press, 2017)
Intra and inter-cellular calcium signaling is present in all types of cells and body tissues. In the human brain, calcium currents and waves are related to mental activities, including emotions. We present a theoretical interpretation of these phenomena suggesting their involvement in chronic emotional patterns and in the pathology of cancer. Recent developments on biophysics, translational biology and psychoneuroendocrinoimmunology (PNEI) can support explanatory hypotheses about the link between emotional stresses and the origin and development of different types of tumor cells. Chronic stresses may cause perturbations of rhythms of the PNEI system, excessive activation of HPA axis and abnormal activation of calcium signals in somatic tissues, with deleterious effects on different parts of the body. The increasing of calcium signaling inside cells may lead to a deregulation of different pathways and epigenetic systems that promote the production of genomic mutations in a second phase. In particular, the hyperactivation of the transcription nuclear factor kappaB (NF-kappa B), if is not counterbalanced by the following activation of the nuclear factor (erythroid-derived 2)-like 2 (NFE2L2 or Nrf2), increases the production of oxidative catabolites, as the advanced glycation end products (AGE), which play a key role in the progression of different types of cancer and other degenerative diseases. Cortisol binding to glucocorticoid receptor (GR) reduces the activity of both NF-.B and Nrf2 inside the cells but inhibits the cellular immunity and the anabolic processes of tissue regeneration. The tissue atrophy and the defective anti-ageing mechanisms promotes the tumoral cells growth and their escape from the immune-surveillance.
Keywords: Calcium signaling; chronic emotion; cancer; psychoneuroendocrinoimmunology; translational biology